PENERAPAN MODEL PEMBEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 004 PADANG MUTUNG KECAMATAN KAMPAR - Upik Rosmiati; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study departed from low yields learn science, with the average achieved learning outcomes at 65.50 with the percentage of 43.33% completeness. The low yield is due to the study: (1) students feel bored, passive, and does not have the initiative to resolve an issue that is given by the teacher, so that in solving a problem the students were only waiting for an answer from the teacher or other students; (2) learning activities in science subjects are not oriented to students but still oriented or centered on the teacher (teaching center); and (3) the learning process is centered on the teacher and the only important or oriented on the end result rather than the process of student learning. Based on this the researchers conducted a study class action by applying inquiry learning model. This research was conducted at SDN 04 Padang Mutung Kecamatan Kampar, with research subjects class V students with the enrollment of 30 students, with details of 13 male students and 17 female students. This research was conducted as many as two cycles, data collection techniques used were observation and written tests. The study states that the implementation of inquiry learning model can increase the activity of teachers and students and learning outcomes IPA. This is evidenced by: (a) mastery learning students has increased, the base score increased to 19 people in the first cycle, then increased to 25 people in the second cycle. The average learning outcomes increased from a base score is 55.67 into 72.00 in the first cycle and 76.50 in the second cycle; (B) the activities of teachers in the first cycle teacher meeting I earn a percentage of 57.50% in the first cycle II meeting to obtain a percentage increase of 65.00%. In the second cycle was a meeting I earn a percentage of 75.00% and in the second meeting of the second cycle gained 87.50%; and (c) the activity of students in the first cycle teacher meeting I earn a percentage of 60.71% in the first cycle II meeting to obtain an increase of the percentage of 75.00%. In the second cycle was a meeting I earn a percentage 82.14% and in the second meeting of the second cycle gained 89.29%. Based on this implementation of inquiry learning model can improve learning outcomes fifth grade IPA students at SDN 04 Padang Mutung Kecamatan Kampar Keywords: Inquiry Learning Model, Learning Outcomes IPA